Interfacial charge transport behavior and thermal profiles of vertically oriented graphene‐bridged supercapacitors. Issue 6 (24th February 2017) - Bo, Zheng; Wu, Shenghao; Qian, Jiajing; Pu, Haihui; Chen, Junhong; Yan, Jianhua; Cen, Kefa
Abstract : Thermal generation induced by Joule heat is detrimental to the lifetime expectancy of a supercapacitor. In this work, the interfacial charge‐transport behaviors and the thermal profiles of vertically oriented graphene (VG)‐bridged supercapacitors, i.e., VGs as the electronic bridges connecting active materials and current collectors, are investigated. Density‐functional theory (DFT) simulations, as well as the calculations based on a combination of DFT and nonequilibrium Green's function (DFT‐NEGF), are conducted to explore the electronic density of states, electron distributions, formation energies, eigenchannels, and electronic transmissions at the solid/solid interfaces of VG‐bridged supercapacitors. The equivalent series resistance, voltage drop, and temperature rise during galvanostatic charging/discharging processes, are measured and compared between the supercapacitors fabricated with and without VG bridges. The results show that the addition of VG bridges can enhance the orbital interactions and the electronic conductivity at the solid/solid interfaces, manifested by a 1–2 orders of magnitude increase of the exchanged charge number, and the significantly enhanced interfacial formation energies as well as the elevated electronic transmission. It further results in the obvious reduction of both the contact resistance and Joule heat generation during the charging/discharging processes.